Bacteriophage-based biosensors technology: Materials, fabrications, efficiencies and shortcomings - Ihtisham Ul Haq; Kashif Rahim; Sajida Maryam; Najeeba Parre Paker (Biotechnology Reports, 2025)
Ongoing research in biosensor technologies has led to advanced functional materials for healthcare diagnostics, and bacteriophages (phages), demonstrating exceptional utility due to their high specificity, accuracy, rapid, label-free, and wireless detection capabilities with minimal false-positive results. Phage-based-pathogen-detecting biosensors (PBPDBs) include surface plasmon resonance (SPR) biosensors, magnetoelastic (ME), electrochemical, and quartz crystal microbalance (QCM) biosensors. Commonly used substrates for PBPDBs are gold, silicon, glass, carbon-based materials, magnetic particles, and quantum dots. These substrates are chemically and physically modified to optimize phage orientation on sensor surfaces, enhancing bacterial capture. To address typical stability and issues encountered in traditional biosensor applications, phage particles and genetically modified phages are utilized to improve biosensor stability and increase detection efficacy while reducing assay time. Genetic modification in phages facilitated by CRISPR/Cas9 enables the tailoring of phages to target specific bacterial strains. This approach helps overcome the inherent specificity of phages and enables the detection of multiple pathogens in a single assay. Multiple pathogens can be detected through a single phage-based assay. This manuscript elucidates the fabrication methodologies and detection efficiencies of PBPDBs providing valuable insights into the development of practical, precise, and efficient biosensors for pathogen detection. Summary: PBPDBs are emerging diagnostic tools for the detection of bacterial pathogens.